2014
DOI: 10.1007/s00702-014-1281-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor symptoms in Chinese Parkinson’s disease patients with and without LRRK2 G2385R and R1628P variants

Abstract: Non-motor symptoms (NMS) are common among patients with Parkinson's disease (PD). However, reports on NMS in Chinese PD population are scarce. Little is known about NMS in patients with Asian specific leucine-rich repeat kinase 2 (LRRK2) variants in G2385R and R1628P. This study aimed to elucidate the clinical characteristics of NMS in Chinese PD patients and to ascertain if there were differences in NMS between PD patients with and without LRRK2 variants. A multicenter, observational study was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…This feature is in line with other series that reported more sleep onset insomnia, few or no rapid eye behavior disorders, and less nocturia in LRRK2 G2019S carriers [4143]. …”
Section: Discussionsupporting
confidence: 92%
“…This feature is in line with other series that reported more sleep onset insomnia, few or no rapid eye behavior disorders, and less nocturia in LRRK2 G2019S carriers [4143]. …”
Section: Discussionsupporting
confidence: 92%
“…Access to medical care and in particular to neurologists is highly variable across different Asian countries and also could influence the expression of NMS. Li et al [23] identified that every PD patient reported at least one NMS, and this high prevalence might be explained by late referrals and insufficient knowledge about PD, which is in line with the conclusions drawn by Zhang et al [24]. …”
Section: Discussionsupporting
confidence: 78%
“…For instance, LRRK2 mutations have shown to be more prevalent in white Caucasian compared to Asian patients. However, Li et al [23] concluded in their study that genetic differences might not play a key role in the presentation of NMS. This, therefore, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies have reported that olfactory function is less impaired in genetic PD with the leucine-rich repeat kinase 2 (LRRK2) G2019S variant than idiopathic PD in Caucasians [5][6][7][8], while little information is available on olfactory function in PD patients with the Asiaspecific LRRK2 G2385R variant. Previous studies have shown that the LRRK2 G2385R variant is commonly associated with late-onset sporadic PD, which is clinically similar to idiopathic PD in Chinese patients [9,10]. Here we carried out a preliminary study to investigate the effects of the LRRK2 G2385R variant on olfaction in PD patients and healthy elderly controls.…”
Section: Introductionmentioning
confidence: 87%